Tinjauan Yuridis Pengalihan Uang Kembalian Konsumen Dalam Bentuk Donasi Oleh Pelaku Usaha Retail Ditinjau Dari Undang-Undang Perlindungan Konsumen Nomor 8 Tahun 1999 di PT Sumber Alfaria Trijaya tbk Keluruahan Lahi Lai Bissi Kopan (llbk) dan Fatululi Kota - Rahman, Arthur Geraldo; Mauritsius, Darius; Pello, Helsina Fransiska (Artemis Law Journal, 2024)
The main problems in this writing are as follows: (1) What are the reasons for the transfer of consumer change in donations? (2) What is the procedure for withdrawing donations for the remaining fractions of consumer change coins at PT Sumber Alfaria Trijaya Tbk? (3) What are the obstacles and solutions to returning the remaining fractions of coins in transactions at PT Sumber Alfaria Trijaya Tbk? This type of research is empirical research conducted in This research was conducted at the place of business actors PT Sumber Alfaria Trijaya Tbk/Alfamart LLBK and Fatululi Villages, Kupang City, East Nusa Tenggara Province and the data source used was primary data. Primary data is data obtained directly from the research location through direct interviews with respondents. Based on the results of this study, it can be seen that (1) The following are some of the reasons for diverting consumer change, availability of small change, ease of transactions, store policy and reducing the loss of small change. (2) After the shift change or completion of working hours, the bank will collect all sales transactions, sales and donations every 2 or 3 days. Furthermore, it will be processed by the parent Alfamart Company in each province, then channeled to the Alfamart head office of the welfare care program, and given to the people in need through the Alfamart care program. (3) (obstacles) in the transfer of consumer change, there are still often some employees (unscrupulous) who do not carry out their duties properly, such as misusing consumer donations for their personal interests and not recording the donation money in the monitor. (Solution) Regarding the existence of dishonest cashier employees, the company should take actions such as, often conducting work checks at each Alfamart outlet, and if it has occurred, it should immediately give a firm warning and sanction to the employee, always routinely checking and disciplining employees